Biopoder, defesa social e COVID-19: a política de gestão da vida e da morte no sistema penitenciário goiano entre 2020 e 2022 - Ferreira, Ana Paula Félix (2025)
This research addresses the theme of how the government of Goiás dealt with the management of the COVID-19 pandemic in state prisons. During the health crisis, prevention and containment measures were adopted, such as mass testing, isolation and hygiene protocols, provision of personal protective equipment, and vaccination for inmates. In this context, the National Council of Justice (CNJ) and courts throughout the country, through the Monitoring and Inspection Groups of the Prison System and the Socioeducational Measures Execution System (GMF), released information about the pandemic situation in their respective federative units through Local COVID-19 Monitoring. Based on this, the objective was to verify if there was a neglect approach regarding the state's management in relation to the lives of detainees, that is, if the policies adopted were effective, based on the analyzed documents. Therefore, bibliographic and documentary research methodologies were used, through a qualitative-quantitative approach. A literature review was conducted to theoretically support the research, and data on COVID-19 infection cases in Goiás state prisons were collected and analyzed. In addition, information was collected from official documents and regulations related to the health of the prison population, which were adopted by the government of Goiás to contain the spread of COVID-19. This methodology allowed understanding the management of the health crisis in the context of the prison system in Goiás and verifying if the containment and prevention mechanisms established in the official regulations and protocols of the World Health Organization were effectively implemented